Tungstate-modulated Ni/Ni(OH)2 interface for efficient hydrogen evolution reaction in neutral media. Issue 3 (17th November 2020) - Tang, Yuanhao; Dong, Lin; Wu, Hao Bin; Yu, Xin-Yao
Abstract : The intercalated tungstate enhances the neutral HER activity and stability of the Ni/Ni(OH)2 interface by tuning its electronic structure. Abstract : Developing highly efficient and low-cost electrocatalysts for the hydrogen evolution reaction (HER) in neutral media is crucial but still a significant challenge on account of the sluggish multistep reaction kinetics involved. Theoretically, constructing a metal/metal hydroxide interface with a metal hydroxide acting as a water dissociation promotor and a metal as the subsequent hydrogen adsorption site is expected to accelerate the HER kinetics in neutral media. We found that the intercalation of tungstate into Ni(OH)2 can tune the electronic structure of the Ni/Ni(OH)2 interface, decrease the energetic barrier for the Volmer step, and thus optimize the HER performance of Ni/Ni(OH)2 hybrid. Herein, a heterostructured Ni/Ni(OH)2 nanosheet array on Cu foam is designed and constructed via a simple hydrothermal and subsequent plasma reduction strategy. The HER performance can be further enhanced by assembling tungstate-intercalated Ni/Ni(OH)2 hybrid nanosheets on Cu2 O nanotube arrays, exhibiting a low overpotential (39 mV @ 10 mA cm −2 ) and excellent stability (48 h).